2004
DOI: 10.1093/bioinformatics/bth178
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of the transcriptional regulatory network in the yeast cell cycle

Abstract: Matlab code and test data are available at http://www.ee.nthu.edu.tw/~bschen/quantitative/regulatory_network.htm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 48 publications
1
93
0
Order By: Relevance
“…It has been shown that TF binding usually affects gene expression in a nonlinear fashion: below some level it has no effect, while above a certain level the effect may become saturated [29,30]. Thus, the regulation function z j [ t ] was modeled as the sigmoid function, which is one kind of Hill function, of y j [ t ] (the protein activity profiles of transcription factor j ) [3,16,30-33]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that TF binding usually affects gene expression in a nonlinear fashion: below some level it has no effect, while above a certain level the effect may become saturated [29,30]. Thus, the regulation function z j [ t ] was modeled as the sigmoid function, which is one kind of Hill function, of y j [ t ] (the protein activity profiles of transcription factor j ) [3,16,30-33]…”
Section: Resultsmentioning
confidence: 99%
“…Though many studies have focused on gene regulatory networks [3-6] and on signaling transduction pathways [7-9], few works have combined these two kinds of networks. Yeger-Lotem and Margalit [10] used classical graph algorithms to integrate the cellular networks of protein-protein and protein-DNA interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2004) used the nonlinear additive model (2) to model the transcription rate of a target gene as a combination of a set of regulatory functions from relevant regulators. Here the response Y is the transcription rate of the target gene; the covariate X j is the gene expression of the j -th regulator; the intercept β 0 is the basal expression of the target gene; and the coefficient β j is the regulatory capability from the j -th regulator.…”
Section: Application To Identify Gene Regulationsmentioning
confidence: 99%
“…The usage of the sigmoid function model to describe a GRN has been discussed in literature, for example, Mestl et al (1995) and Chen et al (2004) among others. An example of the simple sigmoid function is…”
Section: Introductionmentioning
confidence: 99%